Tingkat kesesuaian latihan bahasa Prancis dalam situs pembelajaran apprendre.tv5monde.com dengan capaian pembelajaran bahasa Prancis tingkat A2 di SMA - Nur Dwi Cahyani, Ismi; Ekowati, Sri Harini; Ratna (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2023)
This study aims to determine the suitability of French exercise in apprendre.tv5monde.com learning sites with the achievement of learning French at the A2 level in high school. In an effort to maximize the objectives of the independent learning curriculum, apprendre.tv5monde.com learning site is one of the alternative learning resources that provides French exercises to support students in learning French independently and freely. However, the use of learning sites as learning resources should be in accordance with learning outcomes so that learning objectives can be achieved properly. This research is a qualitative research using content analysis techniques and documentation studies as data collection techniques. The data source used is French practice on the apprendre.tv5monde.com site. The data that has been collected was analyzed using the checklist method. The results of this study indicate that there are 34 exercises that are in accordance with the learning outcomes of high school French level A2 based on CECR from a total of 41 exercises. The results of the analysis are then calculated using a percentage calculation with a percentage result of 82.92%. Thus, according to the criteria for percentage of conformity by Arikunto (2006), French exercises on learning sites apprendre.tv5monde.com in accordance with the learning outcomes of A2 level high school.